AN INVESTIGATION OF SOIL PHYSICO-CHEMICAL VARIABLES ACROSS DIFFERENT LOWLAND FOREST ECOSYSTEMS OF BRUNEI DARUSSALAM - Md. Jaafar, Salwana; Sukri, Rahayu Sukmaria; ProcheÅŸ, Åžerban (Malaysian Journal of Science, 2016)
Tropical forests undisputedly harbor the largest share of global plant diversity, but the mechanisms of maintenance for this diversity cannot be well understood without good data on environmental variables, primarily soil characteristics. This study investigates differences in soil physico-chemical properties in various tropical lowland forest types in Brunei Darussalam, in the Northwest Borneo plant diversity hotspot. Nine different vegetation types were investigated: intact primary mixed-dipterocarp forest, old disturbed secondary forest, young disturbed secondary forest (partly invaded by alien Acacias), heath (Kerangas) forest, peat swamp forest, swampy heath (Kerapah) forest, core mangrove, fringe mangrove and island mangrove forests. Nine 60 x 20 m plots were set up, and sampled for soils at topsoil (0-15 cm depth) and subsoil (15-30 cm depth) layers. Soil gravimetric water and organic matter content, texture, nutrient concentrations, pH, and salinity were determined. The peat swamp and core mangrove forests recorded highest soil nutrient concentrations. Peat swamp forest had the highest GWC, OM content, total N, and total Ca recorded, whereas the soil in core mangrove forest had higher total P, total Mg, total K, exchangeable Mg, exchangeable Ca, exchangeable K and salinity compared to the other habitat types. These results were also highlighted by the principal component analysis for the soil parameters measured. The most nutrient-poor soils were found in the Kerapah and heath forest sites. The difference between topsoil and subsoil for soil variables were generally not significantly different from each other. The present study has shown that soil physico-chemical properties differ significantly between the nine vegetation types studied, and this may have important implications upon differences seen in plant community compositions in these vegetation types. Keywords: Heath forest, Mangrove forest, Mixed Dipterocarp forest, Peat swamps, Edaphic